PENGARUH PERUBAHAN SOSIAL DAN PERKEMBANGAN PARIWISATA TERHADAP PEREKONOMIAN MASYARAKAT DESA KURAU BARAT KECAMATAN KOBA KABUPATEN BANGKA TENGAH - Reza Fahlevy; Reza Tiara Saputri (Jurnal Pendidikan Ilmu Sosial, 2019)
The development of tourism resulted in social changes in the Kurau Barat Village community. This observation aims to find out, describe and explain the social changes that occur in the community in Kurau Barat Village, Koba District. The results of the observations show that the development of tourism was well received by the residents of Kurau Barat Village. Factors that influence social change are acceptance of new elements, accepting acculturation, migration, accepting changes in life habits from traditional to semi-modern, the existence of respect for the work of others and the desire to progress. These changes can affect the sustainability of tourism and the condition of society in the future so that it needs to be directed and managed properly by all parties involved. A qualitative approach is used in discussing social change. Data is collected through observation.